Signal suppression/enhancement in high-performance liquid chromatography tandem mass spectrometry - Gosetti, Fabio; Mazzucco, Eleonora; Zampieri, Davide; Gennaro, Maria Carla (Journal of Chromatography A, 2010)
The review discusses the pitfalls of the matrix effect in mass spectrometry detection hyphenated to liquid chromatography separation. Matrix effect heavily influences both qualitative and quantitative analyses, giving rise to suppression or enhancement of the signal. As generally recognised, the predominant cause is the presence of undesired components that co-elute in the chromatographic separation and alter the ionisation process. The interfering species can be components of the sample, compounds released during the pre-treatment/extraction process or reagents added to the mobile phase to improve chromatographic resolution. The different mechanisms proposed in literature to explain the suppression or the enhancement of the signal both in electrospray and atmospheric pressure chemical ionisations are presented and the results observed in the different experimental conditions are compared and discussed. All data together lead to conclude that the chemical properties of the target analyte, the kind of matrix, the matrix to analyte concentration ratio, the extraction process, the chromatographic conditions as well as the kind of the mass spectrometry instrumentation and the ionisation conditions can play a role. Likely all these potential causes act in a synergic way and the final effect observed is hardly due to only one of them. Depending on an unpredictable combination of conditions, signal suppression or enhancement can be observed. The review discusses the matrix effects observed in HPLC–MS and HPLC–MS/MS analysis proposes hypotheses to explain the observed behaviours and proposes methods and strategies to overcome the matrix effects.